Exploring the mental well-being of Ekurhuleni primary healthcare clinic managers during COVID-19 - Sanele E. Nene; Siyabulela N. Wopula (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2025)
Background: The coronavirus disease 2019 (COVID-19) pandemic extensively disrupted the management dynamics and stretched the mental well-being of Ekurhuleni primary healthcare clinic managers. Their workload was increased, and they also had to deal with the grief of losing colleagues, family members and patients in large numbers as a result of the pandemic.